2010
DOI: 10.1590/s0004-282x2010000200022
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic pattern of patients with neurocysticercosis diagnosed by computed tomography in Curitiba, Brazil

Abstract: The aim of this study was to drawn an epidemiological pattern of neurocystisticercosis (NCC) patients diagnosed by computed tomography at the major private diagnostic center in Curitiba, Brazil. A total of 1,009 medical files of consecutive patients presenting neurological indications were diagnosed by computed tomography from July 2007 to April 2008. Patient data included sex, age, municipality and tomography findings were analysed by Epi-info version 6.0.1. software. Most patients (81.10%) were living in Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The relationship between sex and NCC infection risk is controversial. Some studies showed a higher frequency of the disease in males (Chimelli et al, 1998;Chagas et al, 2003;Lino-Junior et al, 2007;Almeida and Torres, 2011), while others showed a higher prevalence of NCC in females (Pfuetzenreiter and Avila-Pires, 1999;Mendes et al, 2005;Benedeti et al, 2007;Grazziotin et al, 2010;Coral-Almeida et al, 2015). A previous literature review on NCC epidemiology in Brazil showed a higher prevalence of NCC among males, with more frequent involvement of severe manifestations in female patients (Agapejev, 2003(Agapejev, , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between sex and NCC infection risk is controversial. Some studies showed a higher frequency of the disease in males (Chimelli et al, 1998;Chagas et al, 2003;Lino-Junior et al, 2007;Almeida and Torres, 2011), while others showed a higher prevalence of NCC in females (Pfuetzenreiter and Avila-Pires, 1999;Mendes et al, 2005;Benedeti et al, 2007;Grazziotin et al, 2010;Coral-Almeida et al, 2015). A previous literature review on NCC epidemiology in Brazil showed a higher prevalence of NCC among males, with more frequent involvement of severe manifestations in female patients (Agapejev, 2003(Agapejev, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-specific healthcare seeking behaviour may also play a role. The more frequent occurrence of clinical manifestations in women would lead them to seek medical assistance more frequently and, consequently, to carry out more diagnostic testing than men (Pfuetzenreiter and Avila-Pires, 1999;Grazziotin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether a tumor is primary or not, and the primary site of metastatic tumors, immunohistochemical analysis can be used, with specific markers for each tissue and cell. 6 The use of multiple markers may increase the sensitivity, specificity and positive predictive value in predicting the tissue of tumor origin. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The costs due to neurocysticercosis treatment and complications in Brazil may reach up to US$ 85 million. 6 …”
Section: Introductionmentioning
confidence: 99%